Blended SORT-IT for operational research capacity building: the model, its successes and challenges. Issue 1 (1st January 2018) - Decroo, Tom; Van den Bergh, Rafael; Kumar, Ajay M. V.; Zachariah, Rony; Schillberg, Erin; Owiti, Philip; van den Boogaard, Wilma; Benedetti, Guido; Shah, Safieh; Ali, Engy; Harries, Anthony D.; Reid, Anthony J.
ABSTRACT: The Structured Operational Research Training Initiative (SORT-IT) has been shown to be very effective in strengthening capacity for conducting operational research, publishing in scientific journals and fostering policy and practice change. The 'classic' model includes three face-to-face modules during which, respectively, a study protocol, a data analysis plan, and a manuscript are elaborated. Meanwhile, the lectures of the SORT-IT are available online as YouTube videos. Given the availability of this online material and the experiences with online mentorship of the faculty, we piloted a first blended distance/residential SORT-IT. To inform future implementers of our experience with blended operational research courses, we summarize the model, successes, and challenges of this approach in this perspective paper. The blended SORT-IT consisted of an online phase, covering modules 1 and 2, followed by a face-to-face writing module 3. Four out of six participants successfully completed the course, and submitted a manuscript to a peer-reviewed journal within four weeks of completing module 3. A blended approach may make the SORT-IT course more accessible to future participants and may favour the adoption of the course by other institutions, such as national Ministries of Health.